Training opportunities in thoracic ultrasound for respiratory trainees: are current guidelines practical?. (3rd October 2019) - Stanton, Andrew E; Evison, Matthew; Roberts, Mark; Latham, Jennifer; Clive, Amelia O; Batalla-Duran, Elizabeth; Bhatnagar, Rahul; Asciak, Rachelle; Diggins, Ben; Bintcliffe, Oliver J; Lees, Diana; Parsonage, Maria; et al.
Abstract : Introduction: Respiratory trainees in the UK face challenges in meeting current Royal College of Radiologists (RCR) Level 1 training requirements for thoracic ultrasound (TUS) competence, specified as attending 'at least one session per week over a period of no less than 3 months, with approximately five scans per session performed by the trainee (under supervision of an experienced practitioner)'. We aimed to clarify where TUS training opportunities currently exist for respiratory registrars. Methods: Data were collected (over a 4-week period) to clarify the number of scans (and therefore volume of training opportunities) within radiology departments and respiratory services in hospitals in the South West, North West deaneries and Oxford. Results: 14 hospitals (including three tertiary pleural centres) provided data. Of 964 scans, 793 (82.3%) were conducted by respiratory teams who performed a mean of 17.7 scans per week, versus 3.1 TUS/week in radiology departments. There was no radiology session in any hospital with ≥5 TUS performed, whereas 8/14 (86%) of respiratory departments conducted such sessions. Almost half (6/14) of radiology departments conducted no TUS scans in the period surveyed. Conclusions: The currently recommended exposure of regularly attending a list or session to undertake five TUS is not achievable in radiology departments. The greatest volume of training opportunities exists within respiratory departments in a variety of scheduled and unscheduled settings. Revision of the competency framework in TUS, and where this is delivered, is required.